DEVELOPING FLASHCARD MEDIA FOR TEACHING VOCABULARY TO THE SEVENTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL (Study Case in the seventh grade students at SMPN 1 Sanankulon) - Sari, Hesty Puspita; Sutanti, Nita; Wahyuningsih, Linda Tri (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2018)
The aims of this research are not only to know the develop flashcard media for teaching vocabulary to the seventh grade students at SMPN 1 Sanankulon in 2018/2019 academic years but also to know the effectiveness of flashcard media for teaching vocabulary to the seventh grade students at SMPN 1 Sanankulon in 2017/2018 academic years, to know the students response toward the use of flashcard in teaching learning vocabulary to the seventh grade students at SMPN 1 Sanankulon in 2018/2019 academic years. This research is Research and Development (R&D), which used the Sugiyono ’s model (2016:298) with adaptation. The data collecting through interview, questionnaire, documentation, and test. In this case, the researcher used three validators. They are validator of media and validators of material. The product user is VII F of SMPN 1 Sanankulon which consisted of 32 students. In this research, the researcher used one group pre-test and post-test experimental design to try out the product. The result of the research showed that: 1) The result of media validation flashcard and guiding book got the average were 84,37% while the result of content of material validation 87,5%. The average for all validation was 85,41%. The score was catagorized as “very good-- with interval 80% < x â‰¤ 100%. So, the developed flashcard media as a learning media in teaching and learning vocabulary to the seventh grade students was valid to be implemented for the seventh grade students and it can be used as media in teaching learning process especially in vocabulary mastery. 2) It proved by the result of the students ’ test. The mean score of pre-test and post-test increased from 69,81 to the 94,37. It can be concluded that there was increased in mean score before and after treatment. Furthermore, Based on the result of t-test, it showed that value of t-test < t table. So, ho is rejected and ha is accepted. It can be concluded that there is significance of mean score the seventh grade students before and after treatment the product. In other word the product is proper if used in the seventh grade students at SMPN 1 Sanankulon. 3) It proved with result of questionnaire students ’ response. It gained the total score 1038 then the criterion of score 1280. It accumulated on precentage that was 81,09%. It was very good category. It means, that used flashcard media in learning vocabulary is very positive for the seventh grade students. If seen in criteria of response this is absolutely agree response. So, in other word the students absolutely agree if used flashcard media in learning vocabulary.